2021
DOI: 10.1111/1748-8583.12337
|View full text |Cite
|
Sign up to set email alerts
|

Putting the system back into training and firm performance research: A review and research agenda

Abstract: Research investigating training and firm performance is currently at an inflection point; capable of recognising previous achievements but also having a focus on the future. Based on our review of 207 quantitative papers over a 40‐year period, we find that the field has converged in terms of theory and methods. Important insights have been generated yet there is scope to better understand the complex, interrelated and dynamic nature of the relationship between training and firm performance. We propose that ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 168 publications
1
30
0
Order By: Relevance
“…These findings are also likely to be particularly relevant in high power-distance societies like Malaysia, where more direct instruction prevails and is expected by employees (Li et al, 2011). Cognisant of our theoretical justification and operationalisation of an open systems climate as constituting innovation and flexibility, outward focus and reflexivity, these findings suggest we would do well to reincorporate boundary conditions and system dynamics into HRM-system strength research, especially as it related to employee outcomes and attributions of HR (Garavan et al, 2021). Critically, our findings suggest that a sense of openness to change and the quest to align with the external environment may serve to mitigate employee anxiety and foster greater confidence and security manifest among those organisations who may seek a more employee-centric and well-being agenda in the future, especially when coupled with perceptions of a strong internal climate founded on rules and formality.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…These findings are also likely to be particularly relevant in high power-distance societies like Malaysia, where more direct instruction prevails and is expected by employees (Li et al, 2011). Cognisant of our theoretical justification and operationalisation of an open systems climate as constituting innovation and flexibility, outward focus and reflexivity, these findings suggest we would do well to reincorporate boundary conditions and system dynamics into HRM-system strength research, especially as it related to employee outcomes and attributions of HR (Garavan et al, 2021). Critically, our findings suggest that a sense of openness to change and the quest to align with the external environment may serve to mitigate employee anxiety and foster greater confidence and security manifest among those organisations who may seek a more employee-centric and well-being agenda in the future, especially when coupled with perceptions of a strong internal climate founded on rules and formality.…”
Section: Discussionmentioning
confidence: 56%
“…Open systems climate captures a number of dimensions or boundary conditions of direct relevance to HRM research (Garavan et al, 2021). The first includes employee perceptions as related to innovation and flexibility, exploration behaviours and acceptance of new modes of thinking (Panayotopoulou, Bourantas and Papalexandris 2003).…”
Section: The Moderating Role Of Open Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending this employee training is another important HR practice that encourages and engages employees in new activities at the workplace during crises (Memon et al, 2016;Risley, 2020;Sun et al, 2022a). Training is defined as the extent to which the HR department designs training program to enhance employee skills and knowledge, which in turn help in career advancement and achieving high-performance work (Armstrong et al, 2021;Garavan et al, 2021;Park et al, 2022). Prior studies have confirmed the significant impact of HR training on employee work engagement during crises such as pandemic (Armstrong et al, 2021;Azizi et al, 2021;Garavan et al, 2021;Gim et al, 2021;Ishiyama, 2021;Risley, 2020).…”
Section: Hr Compensation and Trainingmentioning
confidence: 99%
“…Training is defined as the extent to which the HR department designs training program to enhance employee skills and knowledge, which in turn help in career advancement and achieving high-performance work (Armstrong et al, 2021;Garavan et al, 2021;Park et al, 2022). Prior studies have confirmed the significant impact of HR training on employee work engagement during crises such as pandemic (Armstrong et al, 2021;Azizi et al, 2021;Garavan et al, 2021;Gim et al, 2021;Ishiyama, 2021;Risley, 2020). Therefore, the following hypotheses are proposed: H1.…”
Section: Hr Compensation and Trainingmentioning
confidence: 99%